AUDIT ENERGI PADA BANGUNAN GEDUNG – STUDI KASUS PADA GEDUNG PERKANTORAN - Chalidia Nurin Hamdani; Astrie Kusuma Dewi; Asepta Surya Wardhana; Primaldi Anugrah Utama; Radityo Cahyo Yudanto; C.F. Pradana Swandaru (Jurnal Teknologi Terapan, 2023)
Energy usage is constanly increasing with regard to technology invention, equipment number growth and people growth. So, we have to do energy conservation. The first step in energy conservation implementation is energy audit. By doing energy audit, we are able to identify energy saving potential in audit object. In this paper, we provide a study case of energy audit in office building in Indonesia performed on 2018. This office building has an area of approximately 1.120 m2 with Rp 10,889,658 of average of energy use per month. Energy audit had performed on electricity system, air conditioning system, lighting system dan energy management system. Energy usage profile had been identified and modeled using linear approximation so the main factor of energy usage can be known. Energy saving potential that can be obtained is about 2.358 kWh (30,45%) with Rp 2,431,359 of cost saving approximation per month or Rp 29,176,308 per year.